The Implementation of Media Sharing Sites in Learning French: A Systematic Literature Review - Mulyanita, Dewisri; Gumilar, Dudung; Darmawangsa, Dante (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Several challenges hinder French language learning, hence diminishing its effectiveness. Consequently, there is a demand for educational tools that are accommodating and efficient, such as media-sharing sites (MSS). MSS has several positive and negative effects. Minimizing adverse effects requires knowledge of factors that can make learning effective. Consequently, this research aims to fulfill this requirement by identifying the variables that affect learning outcomes and students' responses to the implementation of MSS in learning French. This study used a systematic literature review (SLR). Research data was collected from several databases, including Taylor & Francis Online (tandfonline.com), Research Gate (researchgate.net), and RDiscovery (discovery.research.life). Twenty-two articles were selected, extracted, and analyzed for this study. The findings are grouped into two main issues: factors affecting learning outcomes and students' responses. Factors affecting student learning outcomes are grouped into four areas: learning models, systems and features, audio-visual content, and teacher contributions. Thus, students' responses are categorized into three types: cognitive, affective, and conative responses. The results showed that implementing MSS in learning French assisted educators and learners more effectively and efficiently. Furthermore, it was found that there is a correlation between student responses and the future vision of education.